Relevance of reviewing endpoint analysis for negative results on the Xpert Xpress Flu/RSV. Issue 12 (15th April 2020) - Matic, Nancy; Ritchie, Gordon; Lawson, Tanya; Karakas, Loretta; Romney, Marc G.; Lowe, Christopher F.
Abstract: After the implementation of the Xpert Xpress Flu/respiratory syncytial virus (RSV) assay for rapid respiratory molecular testing, we investigated the significance of reported endpoint values for influenza A, influenza B, and RSV). This study prospectively analyzed nasopharyngeal swabs submitted to our virology laboratory in the 2018/19 influenza season. Initial testing was performed on the Xpress Flu/RSV assay. Samples were further tested on a laboratory‐developed multiplex polymerase chain reaction (laboratory‐developed multiplex respiratory test [LDT]) if the sample was reported as negative by the Xpress Flu/RSV but had an elevated endpoint value ≥5 for any respiratory virus target. There were 1040 negative results on the Xpress Flu/RSV; thirty‐one had at least one endpoint value ≥5 [influenza A (25), influenza B (1), RSV (2), influenza A/RSV (1), and influenza A/B/RSV (2)]. Five samples (5/31, 16.1%) were positive on the LDT for influenza A or RSV. In contrast, the positivity rate on the LDT for negative Xpress Flu/RSV samples with endpoint values less than 5 was 0.35% ( P  < .0001). A threshold for endpoint values could not reliably be established to differentiate a potential influenza A positive result from a negative result on the LDT. Routine evaluation ofendpoint values should be a consideration for laboratories implementing Xpress Flu/RSV, in addition to supplementary respiratory virus testing for clinically relevant situations.